2018
DOI: 10.4067/s0718-221x2018005002101
|View full text |Cite
|
Sign up to set email alerts
|

Kraft scrap paper pulp as a substitute of wood chips in manufacture of particleboards resinated with hybrid pf/pmdi resin

Abstract: This study analyzed feasibility of manufacture of composite particleboards resinated with a mixture of phenol-formaldehyde resin and 4,4′-methylenediphenyl isocyanate in the weight ratio 70:30. For this purpose 3-layer particleboards were produced with varying shares of Kraft scrap paper pulp in the core. Experimental boards were manufactured applying 0, 10, 15, 25, 50 and 75% substitution of wood chips with Kraft paper pulp. Analyses were conducted to determine physico-mechanical properties of boards, i.e. be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…This density meets the density requirements for high-density particleboards, which range from 0.60 to 1.45 g/cm³. 39 The thickness ranged from 8 mm. The sisal fibre used had a density of 1.45 g/cm³ and the polyester resin had density of 1.1 g/cm³.…”
Section: Resultsmentioning
confidence: 57%
“…This density meets the density requirements for high-density particleboards, which range from 0.60 to 1.45 g/cm³. 39 The thickness ranged from 8 mm. The sisal fibre used had a density of 1.45 g/cm³ and the polyester resin had density of 1.1 g/cm³.…”
Section: Resultsmentioning
confidence: 57%
“…On the other hand, office paper must be bleached and deinked, to have typical white color. This process is lowering the physical properties of paper and that is why cardboard has better physical and mechanical properties (Dukarska et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…During the processing of recycled wastepaper, it is necessary to get rid of the printing inks and other additives on the material. This deinking process can reduce the strength of the fibers and negatively impact the environment (Dukarska et. al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, pMDI-modified adhesives were also found to be suitable for manufacturing composites from particles other than wood, in the case of which the stronger adhesion is needed to meet the standardized strength requirements. Studies have shown that hybrid adhesives worked well as binding agents for the production of boards made of, e.g., rape straw [21], sunflower husks [22], pine bark [23], waste corrugated paper [24], and kraft paper [25]. The outcomes have shown that, due to the application of PF/pMDI resin, produced composites were characterized by satisfactory mechanical and physical features, which allowed them to fulfill the requirements of proper standards.…”
Section: Type Of Hybrid Resin Type Of Wood-based Materials Effect Of ...mentioning
confidence: 99%